ANALISIS ELEMEN-ELEMEN EKUITAS MEREK (BRAND EQUITY) DARI PRODUK KARTU TELEPON CDMA - Muhammad, Muhammad; Abdurachman, Edi (Bina Nusantara University, 2009)
Globalisation era has commitment a new opportunity and business challenge for companies in Indonesia. On one side, globalisation era expand product market from companies in Indonesia and on the other side that situation has created the competition which more tight between domestic company nor multinational companies. One of the industry who has very tight competency is cdma phone card or telecommunication industry. Indonesia currently has 5 (five) companies in that industry: Bakrie Telecom, Indosat, Telkom, Sinar Mas Group, and Mobile 8. The thesis has objective to do some research on the elements of brand equity from 6 (six) cdma phone card merk who have accomadated by that companies. The benefit from this research is to give some information for readers about which cdma phone card product who has most brand awareness, brand association, brand loyalty, and brand perceived quality. This hypothesis will use independent method T-Test sample, Paired Sample T-Test, and Cohran Test. The result from every elements found Esia card product is the highest score level from brand awareness, cheaper from telephone and sms, and the highest score from brand loyalty is Starone card, the highest score from brand perceived quality based from performance and importance is Starone card.